Prevalence and factors associated with postpartum posttraumatic stress in a population-based maternity survey in England - Harrison, SE; Ayers, S; Quigley, MA; Stein, A; Alderdice, F (Elsevier, 2020)
Background: Studies on prevalence and factors associated with postpartum posttraumatic stress (PTS) typically do not distinguish between PTS related to childbirth (PTS-C) and PTS related to other stressors (PTS-O). This study aimed to describe the prevalence, clinical characteristics, and factors associated with PTS-C and PTS-O in postpartum women.